WASIAT WAJIBAH DAN PERKEMBANGAN PENERAPANNYADALAM PUTUSAN MAHKAMAH AGUNG - Halim, Abdul (Al-Mazaahib: Jurnal Perbandingan Hukum, 2018)
Wasiat wajibah in Article 209 of KHI which is different from the wasiat wajibah existing in other Islamic countries as stated above, in the perspective of ushul fiqh (istihsan) does not violate the provisions of Islamic inheritance law because adopted children and adoptive parents remain positioned not as heirs. The right’s granting to them through a wasiat wajibah that does not exceed 1/3 solely to accommodate local wisdom and to maintain the sense of justice of Indonesian Islamic society. The reconstruction of wasiat wajibah by the Supreme Court to resolve new cases confronted to them by applying the legislative approach with the legal discovery method that is grammatical interpretation method, teleological/sociological interpretation, and argumentum per analogium/analogy in the perspective of ushul fiqh do not violate lugawiyah and ma'nawiyah rules. This reconstruction is very necessary to ensure the certainty and unity of law in accordance with the conditions of the needs and legal awareness of Muslims in Indonesia.